2018
DOI: 10.1111/gove.12352
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and women in cabinets: Informal barriers to recruitment in the executive

Abstract: Research on corruption and women in politics has mainly focused on legislatures, generally finding that corruption decreases the election of women. This article turns the spotlight to the executive branch—an arena where selection is less transparent than recruitment to legislative seats—and examines if corruption decrease the share of ministers who are women. Drawing on feminist institutionalist theories, we posit that in an environment of high political corruption, (male) elites involved in cabinet formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 74 publications
1
12
0
5
Order By: Relevance
“…Several studies have observed that more women are usually elected to the national parliament in countries with less corruption (Dollar, Fisman and Gatti 1999;Bjarnegard 2013;Stockemer 2011). Similar patterns have been observed for women in local councils (Sundstrom and Wangnerud 2016), and cabinets (Stockemer and Sundstrom 2017). Interpreting the underlying reasons for the correlation, and the controls required for well-specified models, remains a matter for debate (Sung 2003(Sung , 2012.…”
Section: The Impact Of Corruption and Clientelismsupporting
confidence: 57%
“…Several studies have observed that more women are usually elected to the national parliament in countries with less corruption (Dollar, Fisman and Gatti 1999;Bjarnegard 2013;Stockemer 2011). Similar patterns have been observed for women in local councils (Sundstrom and Wangnerud 2016), and cabinets (Stockemer and Sundstrom 2017). Interpreting the underlying reasons for the correlation, and the controls required for well-specified models, remains a matter for debate (Sung 2003(Sung , 2012.…”
Section: The Impact Of Corruption and Clientelismsupporting
confidence: 57%
“…The inequality in access to workplace authority is one of the recurring themes explaining the gender pay gap (Stockemer & Sundström, 2019). Glass ceiling-the barriers against women's hiring and advancement to top management-is one of the most commonly used concepts when discussing the gender inequality in executive hiring (Sampson & Moore, 2008).…”
Section: Gender Disparity In Hiringmentioning
confidence: 99%
“…Widening the scope of our studies to include developing countries also substantially increases the number of units whose behavior we can observe, as recent work published in Governance demonstrates (cf. Jindra & Vaz, 2019; Shockley, Ewers, Nardis, & Gengler, 2018; Stockemer & Sundstrom, 2019). The role of international organizations, or, for instance, country performance rankings (see e.g., Kelley & Simmons, 2020) can be better understood, and influences better identified, through an increase in statistical power that is borne of the widening of our cross‐country scope.…”
Section: To Understand Domestic Public Administration Look Beyond Itmentioning
confidence: 99%